The faux in Dickens’ gentlemen : great disappointments and twists in the underbelly of London - Zhang, Samuel Junyang (2009)
How is the Victorian gentleman defined? The concept of the Victorian gentleman is a complex one. According to David Cody, he writes that the “Victorians themselves were not certain what a gentleman was, of what his essential characteristics were, or of how long it took to be one”. The concept of the gentleman is an elastic one and authors such as Charles Dickens and William Thackeray were indeed fascinated with the idea of the gentleman. Their works of fiction often depict their unique perspectives of how and what constitutes to being a gentleman. However, when the fictional portrayal of the gentleman is juxtaposed with the social reality of being a gentleman, the differences and similarities between fiction and reality become evident to the individual. Despite the conflicting depictions and meanings, this essay seeks to consolidate the various images and definition of the Victorian gentleman. I am particularly concerned with how the faux Victorian gentleman is constructed through the individual's desire to climb up the social ladder within the space of London. Though succeeding in their pursuit of gentility, such individuals end up becoming faux gentlemen who stare in the face of alienation and disappointment. And through the running theme of disappointment in Charles Dickens' novel: Great Expectations and Oliver Twist, society's perversions within the space of London are revealed by utilizing the protagonists as a filter and narrator.